함수와 그래프

1971 days 전, sky 작성

plot(1-x^2) 
       
plot(x^3+1) 
       
var('x, y') implicit_plot(x==y^2-1,(x,-2,2),(y,-2,2)) 
       
plot(2*x) 
       
m=3 #93p 4번 b=2 f(x)=m*x+b plot(f(x), xmax=5, xmin=-5, ymax=5, ymin=-5) 
       
m=-2 b=2 f(x)=m*x+b plot(f(x), xmax=5, xmin=-5, ymax=5, ymin=-5) 
       
m=1/2 b=-3 f(x)=m*x+b plot(f(x), xmax=5, xmin=-5, ymax=5, ymin=-5) 
       
m=-5 b=-1/4 f(x)=m*x+b plot(f(x)) 
       
m=-3/4 #93p 5번 b=5/4 f(x)=m*x+b plot(f(x), xmax=5, xmin=-5, ymax=5, ymin=-5) 
       
m=2/5 b=6/5 f(x)=m*x+b plot(f(x), xmax=5, xmin=-5, ymax=5, ymin=-5) 
       
plot(-2, color='purple') 
       
f(y)=-1 plot(f(y), color='red') 
       
m=0 b=-1 f(x)=m*x+b plot(f(x), xmax=5, xmin=-5, ymax=5, ymin=-5) 
       
f(x)=3*x+4*y==5 #93P 5번 (Y절편 구하기) f(0) 
       
4*y == 5
4*y == 5
solve(x + sqrt( x + 5) == 7, x) #계산이 안됨 (104p 4(1)) 
       
[x == -sqrt(x + 5) + 7]
[x == -sqrt(x + 5) + 7]
solve((x-7)^2==(x+5), x) #식을 바꿔주니까 됨 (104p 4(1)) 
       
[x == 4, x == 11]
[x == 4, x == 11]
solve(x-sqrt(13-x)==1, x) #계산이 안됨 (104p 4(2)) 
       
[x == sqrt(-x + 13) + 1]
[x == sqrt(-x + 13) + 1]
solve(x-1==sqrt(13-x), x) #계산이 안됨 (104p 4(2)) 
       
[x == sqrt(-x + 13) + 1]
[x == sqrt(-x + 13) + 1]
solve((x-1)^2==(13-x), x) #식을 바꿔주니까 됨 (104p 4(2)) 
       
[x == -3, x == 4]
[x == -3, x == 4]
f(x)=x+sqrt(x+5) f(4)==7 #성립함(104p 4(1)) 
       
7 == 7
7 == 7
f(x)=x+sqrt(x+5) f(11)==7 #성립하지 않음(104p 4(1)) 
       
15 == 7
15 == 7
f(x)=x-sqrt(13-x) f(-3)==1 #성립하지 않음(104p 4(2)) 
       
-7 == 1
-7 == 1
f(x)=x-sqrt(13-x) f(4)==1 #성립함(104p 4(2)) 
       
1 == 1
1 == 1
solve(x^2 + abs(2*x-1) == 3, x) #105p3(1) 계산이 안됨 
       
[x == -sqrt(-abs(2*x - 1) + 3), x == sqrt(-abs(2*x - 1) + 3)]
[x == -sqrt(-abs(2*x - 1) + 3), x == sqrt(-abs(2*x - 1) + 3)]
solve(x^2-3==-abs(2*x-1), x) #105p3(1) 계산이 안됨 
       
[x == -sqrt(-abs(2*x - 1) + 3), x == sqrt(-abs(2*x - 1) + 3)]
[x == -sqrt(-abs(2*x - 1) + 3), x == sqrt(-abs(2*x - 1) + 3)]
solve(x^2+2*x-1==3, x) #105p3(1) _ 1 계산됨 
       
[x == -sqrt(5) - 1, x == sqrt(5) - 1]
[x == -sqrt(5) - 1, x == sqrt(5) - 1]
solve(x^2-2*x+1==3, x) #105p3(1) _ 2 계산됨 
       
[x == -sqrt(3) + 1, x == sqrt(3) + 1]
[x == -sqrt(3) + 1, x == sqrt(3) + 1]
solve(abs(x^2-1)==x+1, x) #105p3(2) 계산이 안됨 
       
[x == abs(x^2 - 1) - 1]
[x == abs(x^2 - 1) - 1]
solve(x^2-1==x+1, x) #105p3(2) _ 1 
       
[x == 2, x == -1]
[x == 2, x == -1]
solve(-x^2+1==x+1, x) #105p3(2) _ 2 
       
[x == -1, x == 0]
[x == -1, x == 0]
f(x)=2*x-5*y==-6 f(0)/-5 
       
y == (6/5)
y == (6/5)
solve(4*y == 5, y) 
       
[y == (5/4)]
[y == (5/4)]
f(x)=2*x-5*y==-6 f(0) 
       
-5*y == -6
-5*y == -6
solve(-5*y == -6, y) 
       
[y == (6/5)]
[y == (6/5)]
f(X)=y+1==0 f(0) 
       
y + 1 == 0
y + 1 == 0
solve(y+1 == 0, y) 
       
[y == -1]
[y == -1]
implicit_plot(x==-6, (x, -10, 10), (y, -10, 10), axes=True) 
       
implicit_plot(y==5, (x, -10, 10), (y, -10, 10), axes=True)